(untitled) (Journal of the College of Education for Women, 2020)
The research aims to find out the impact of Lee’s cognitive strategy on the achievement of fifth-grade literary students in the module of history. The research community consists of the secondary female day schools of Al-Karkh Al-Oula Directorate General of Education. The size of the research sample comprises (45) female students of the fifth grade of the literary brunch, (21) students for the experimental group and (24) students for the control group. The researchers have chosen an experimental design with partial control to suit the current research and its goal. They used a unified tool to measure the achievement of female students, which consisted of (50) items characterized by sincerity and they extracted the stability of the tool based on the Pearson correlation equation (0.79) and corrected the equation with Syberman (20). The final stability coefficient (0.82), a ratio of stability, which is acceptable in educational and psychological studies. In light of the above, the researchers commenced the experiment application on Wednesday, 19/10/2016. The responses of the students were obtained and the data for the post-achievement test was ready for statistical analysis. The researchers used the following statistical methods (T-test for two independent samples, Pearson correlation coefficient, Cyberman-Brown equation, Kay square test, Paragraph difficulty coefficient, discrimination coefficient and equation of the effectiveness of incorrect alternatives.....